# Solve the following :$\frac{-2}{3} \times \frac{3}{5} + \frac{5}{2} - \frac{3}{5} \times \frac{1}{6}$

Given :

The given expression is $\frac{-2}{3} \times \frac{3}{5} + \frac{5}{2} - \frac{3}{5} \times \frac{1}{6}$

To do :

We have to solve the expression

Solution :

Distributive Property:

The distributive property of multiplication states that when a factor is multiplied by the sum or difference of two terms, it is essential to multiply each of the two numbers by the factor, and finally perform the addition or subtraction operation.

This property is symbolically stated as:

$a (b+c) = a\times b + a \times c$

$a (b-c) = a \times b - a \times c$

Therefore,

$\frac{-2}{3} \times \frac{3}{5} + \frac{5}{2} - \frac{3}{5} \times \frac{1}{6}=\frac{-2}{3} \times \frac{3}{5} - \frac{3}{5} \times \frac{1}{6}+ \frac{5}{2}$

$= \frac{-3}{5} (\frac{2}{3} + \frac{1}{6}) + \frac{5}{2}$

$= \frac{-3}{5} (2\times2+\frac{1}{6}) + \frac{5}{2}$

[LCM of 3 and 6 is 6]

$= \frac{-3}{5} (\frac{5}{6}) + \frac{5}{2}$

$= \frac{-1}{1}(\frac{1}{2}) + \frac{5}{2}$

$= \frac{-1}{2} + \frac{5}{2}$

$= \frac{(5-1)}{2}$

$= \frac{4}{2}$

$= 2$.

The value of  $\frac{-2}{3} \times \frac{3}{5} + \frac{5}{2} - \frac{3}{5} \times \frac{1}{6}$ is 2.

Tutorialspoint

Simply Easy Learning

Updated on: 10-Oct-2022

36 Views